High-Throughput Sequencing to Investigate lncRNA-circRNA-miRNA-mRNA Networks Underlying the Effects of Beta-Amyloid Peptide and Senescence on Astrocytes - Deng, Yuxin; Song, Hui; Xiao, Yan; Zhao, Yi; Chu, Liangzao; Ding, Jiuyang; Shen, Xiangchun; Qi, Xiaolan (Frontiers in Genetics, 2022)
Astrocytes are widely distributed in the central nervous system and play an essential role in the function of neuronal cells, and potential associations between astrocytes and AD have been noted. Recently, circRNA and lncRNA have been widely implicated in the development of AD. However, the lncRNA and circRNA involved in the influence of Aβ and senescence on astrocytes are rarely reported. This study was aimed to study the changes at the transcriptome level and to explore the effects of Aβ and senescence on astrocytes. Primary cultured astrocytes were treated with Aβ and cultured for 90 days in vitro, and high-throughput sequencing was performed to identify differentially expressed RNAs. GO and KEGG enrichment analysis revaled that differentially expressed genes were associated with focal adhesion signaling pathway, ECM recepror signaling pathway and the extracellular matrix. The PPI network was then constructed, and 103 hub genes were screened out, most of them were closely related to ECM, ECM receptor signaling pathway and focal adhesion. Two ceRNA networks were constructed based on the selected hub gene and DERNAs and multiple ceRNA regulatory axes are present in the effects of Aβ and senescence on astrocytes. Taken together, it is the first time to explore the molecular regulation mechanism of Aβ and senescence on primary astrocytes from the perspective of the whole transcriptome and discovered the signaling pathways and biology processes involved in the effects of Aβ and senescence on astrocytes, providing novel insights into the pathogenesis of AD from the aspect of ceRNA network regulation.